Lectura y expresión oral en los estudiantes de décimo de la Unidad Educativa “Carlos Cisneros”, Riobamba - Mazón Pilco, Jessica Johanna (2023)
The present investigation was carried out at the "Unidad Educativa Carlos Cisneros", where a lack of reading practice was observed in the students and with it a deficient oral expression, since the interest in reading has not been promoted to the student in the classroom. Therefore, the objective of this work is to analyze the level of reading and oral expression of 10th grade students in the morning section, as well as to determine applicable didactic strategies for the development of reading and oral expression habits. The proposed study was of a qualitative nature since it is an educational research, with a non-experimental design, since it is carried out without manipulating the variables under investigation: the phenomenon or events will be observed as they are presented in their natural and real context to analyze and interpret them, in addition to the type of bibliographic research because there will be a broad search for information on the topic to be investigated in journals, scientific articles, books, websites, among others, and field research to be conducted in the "Unidad Educativa Carlos Cisneros" located Riobamba city, the study population was thirty-six students. The level of research was diagnostic to determine whether students have the habit of reading to subsequently implement teaching strategies, in addition, techniques such as survey and observation were used through the application of instruments to collect data as the questionnaire of questions and observation sheets respectively prior and after implementing teaching strategies for the development of reading habits and improvement of oral expression. The way to generate a better reading skill is for the student to develop his/her own motivation, so we used texts of the student's preference, as well as a base of books selected according to his/her age, while to develop his/her oral expression we applied the development of imagination and creativity to expose the message to his/her classmates of what was read through the representation of characters, in addition to providing a space for group information exchange. It is recommended that the teacher has the predisposition to acquire new knowledge, since the application of teaching strategies will help the students to develop reading habits.